Implementasi Kebijakan Kota Tanpa Kumuh Di Kota Manado (Studi Pada Kelurahan Perkamil Kecamatan Paal Dua) - Monalisa A. Kumeang; Elfie Mingkid; Antonius Purwanto (Sam Ratulangi University, 2022)
This research aims to analyze and describe the implementation of the “Kotaku” policy in Perkamil Village, Paal Dua sub-District, Manado City, in terms of Adequate resources, How many causal relationships occur and, Authority/power. The method used in this study is descriptive qualitative and the collection technique is by observation, interviews and documentation. The informants in this study were the Head of the Residential Area of Manado City Devision , the Head of the Mando City Housing Division, the Head of the Manado City Civil Service Police Unit Devision, the Head of the Paal Dua Sub-district, the Head of Perkamil Village, the Head of the Environment IV , and VI Perkamil Village and Community of Perkamil Village, Paal Dua sub-District, Manado City. The results of this study indicate that Financial aspects/budgets are less supportive. Lack of social awareness of the community in participating in protecting, caring and preserving the results of the development of slum settlements, as well as the economic level of the community in Perkamil Village is still low. Lack of community participation in Perkamil Village in participating in counseling programs, socialization.